Absconditella fossarum and A. sphagnorum (Lichenes, Stictidaceae) in NW Poland - Mirosława Ceynowa-Giełdon (Acta Mycologica, 2014)
The paper presents Absconditella fossarum, a species new to Poland, found on sands in the Noteć river valley and A. sphagnorum from the new stands found on peated shore of pure, forest lakes in the Tuchola Forest (Bory Tucholskie) region.